Multiplicidade : o lugar da habitação nas intervenções em áreas centrais - Trindade, Fernanda Cota (2015)
Most of Brazilian cities urbanization processes are strongly define by social and spatial segregation, which can influence directly in the way that habitation locates in the urban space. The real estate speculation, the ineffective habitation’s politics,